2016
DOI: 10.1007/s10456-016-9500-2
|View full text |Cite
|
Sign up to set email alerts
|

Tumor vasculogenic mimicry predicts poor prognosis in cancer patients: a meta-analysis

Abstract: The presence of VM predicts poorer survival outcomes in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 63 publications
3
90
0
Order By: Relevance
“…Most notably, melanoma cells can align along a deposited basement membrane forming interconnecting vessel‐like structures with lumen, a process known as vasculogenic mimicry (VM). First described in 1999 in uveal melanoma, 94 VM is considered a signature of aggressive cancers, and the occurrence of VM has now been found to correlate with poor prognosis in many cancers such as cutaneous melanoma, breast cancer and glioblastoma 95 . Moreover, it is observed that VEGF inhibition resulted in adaptive resistance in melanoma xenografts, in turn leading to increased VM 96 .…”
Section: Vasculogenic Mimicry Channels: An Alternative Route Of Leukomentioning
confidence: 99%
“…Most notably, melanoma cells can align along a deposited basement membrane forming interconnecting vessel‐like structures with lumen, a process known as vasculogenic mimicry (VM). First described in 1999 in uveal melanoma, 94 VM is considered a signature of aggressive cancers, and the occurrence of VM has now been found to correlate with poor prognosis in many cancers such as cutaneous melanoma, breast cancer and glioblastoma 95 . Moreover, it is observed that VEGF inhibition resulted in adaptive resistance in melanoma xenografts, in turn leading to increased VM 96 .…”
Section: Vasculogenic Mimicry Channels: An Alternative Route Of Leukomentioning
confidence: 99%
“…It is intriguing to find that both tumors in this series were monosomy 3 and exhibited vasculogenic mimicry patterns: genetic and histopathological findings that have been associated with an aggressive clinical course [15,16]. However, it should be emphasized that both patients in this study are alive and metastasis free 9 years following enucleation.…”
Section: Discussionmentioning
confidence: 74%
“…In tumor cellformed vessels, blood passes through basement membrane-lined vascular networks with tumor cells sitting exterior to the membrane matrix, while traditional vessels support blood flowing through endothelial cells lining the vasculature with the basement membrane exterior to the cells. The light microscopic morphological characterization of VM in patient tumors showed matrix-rich channels containing plasma and RBCs lined by melanoma cells, and noteworthy poor clinical outcome in patients where VM was identified (14). Because VM is associated with the aggressive tumor cell phenotype and advanced stage disease, it is hypothesized that this extravascular perfusion pathway serves as a growth advantage and escape route for rapidly growing tumor cells.…”
Section: Melanoma Vascular Phenotypementioning
confidence: 99%